Hyperuricemia in Obese Children: Diagnostic Challenges, Pathophysiological Mechanisms, and Therapeutic Approaches - systematic review of current literature - Borończyk, Agnieszka; Bioły, Anna; Marcjasz, Piotr; Buliszak, Agnieszka; Babczyńska, Monika; Kucia, Karolina; Hrapkowicz, Roksana; Zając, Piotr (Quality in Sport, 2025)
Hyperuricemia in children with obesity is an increasingly common health issue, strongly associated with the development of various metabolic and cardiovascular diseases. It serves as a significant risk factor for conditions such as hypertension, type 2 diabetes, and chronic kidney disease. This study aimed to conduct a comprehensive review of the existing literature on the relationship between hyperuricemia and childhood obesity, adhering to the PRISMA guidelines for systematic reviews. The primary mechanisms leading to hyperuricemia in this context include insulin resistance, lipid disorders, and impaired renal function. This article discusses several risk factors contributing to elevated uric acid levels in obese children, including a diet high in purines, excessive fructose intake, and a lack of physical activity. Additionally, it presents available diagnostic methods, such as measuring serum uric acid concentration and supporting tests like lipid profiles and renal function assessments. The article also explores preventive interventions, which encompass dietary and lifestyle modifications, as well as the early implementation of pharmacological treatments, such as allopurinol or metformin. Furthermore, it emphasizes the necessity for ongoing clinical research to develop more effective strategies for the treatment and prevention of hyperuricemia in obese children.